Une innovation institutionnelle, la constitution des communs du logiciel libre - Pierre-André Mangolte (Revue de la Régulation)
Today, free software has become a benchmark for resistance to the “tragedy of the anti-commons”. The sharing and reuse of source code are indeed principles opposed to the exclusive control of technical objects by individual owners. Inventing licenses which diverts copyright and rules of “intellectual property”, free software programmers were able to create a commons (a stock of software) to which anyone may add but from which no one may subtract which everyone can add something. One can speak of a true institutional innovation and an authentic common. The article traces the history of the formation of free software by highlighting the original features of this common understanding as a set of resources, more or less perennial, to which access and use are shared in a group, and here, this group is formally all mankind. It discusses the constitutional basis of the common, the free software (or open source software) licenses and their rules, founding of a particular economy. It sets limits and draws a map of this common.